Ґенеза карпатизму кошара - Пашкова, Надія (Slavia Orientalis, 2020)
The purpose of the article is to study the origin and spread of the Carpathism koshara in Slavic and Balkan languages and within Carpathian dialects. The material used in the analysis comprises general, specialist and dialect dictionaries, as well as dialectological atlases and maps. The study has used methods of semantic and phonetic analysis of lexicographic sources, an interpretation of linguistic maps as well as etymological analysis. A comparative‑historical study of the word koshara allows one to determine such a development of meaning: “the result of weaving, something woven”. Then there was a transfer to capacity and, finally, specialization: “capacity for carrying things, basket”, “capacity for body, clothes”, “capacity for housing, house”, “housing for people”, “housing for animals”. The comparative‑historical research conducted involving broad dialectical material has allowed one to finally accept the еastern etymology of the word from the turс. koš, related to the verb košmak.
Keywords: Carpathian dialects; Slavic languages; Balkan languages; the word for sheep pen